Communicating culinary desire: persuasive strategies in Netflix's 'Flavoured Origins' - Henricus Hans Setyawan Prabowo; Md. Anisul Haque; Misbah Ul Islam (Pascasarjana Institut Seni Indonesia Surakarta, 2025)
Food documentaries have become influential tools for cultural representation on streaming platforms, yet little is known about how they construct culinary authenticity and engage viewers psychologically. This paper examines how Netflix's Flavorful Origins uses persuasive visual strategies to communicate culinary desire while representing regional Chinese cuisines. Three episodes (